Why remit? The case of Nicaragua - George S. Naufal (Institute for the Study of Labor (IZA), 2008)
In the last two decades remittances have gained interest due to their large size. For several developing countries remittances constitute a large portion of their GDP and sometimes exceed FDI. While FDIs are usually profit driven, it is not clear what the driving force behind remittances is. This paper presents a simple theoretical model of migrants' remitting behavior. I consider two general motivations for remitting: altruism and self-interest. Using a heteroskedastic Tobit with a known form of variance I test the findings of the theoretical model with data from Nicaragua. Evidence suggests that migrants from Nicaragua remit for altruistic reasons. Moreover some gender heterogeneity seems to exist in the remitting behavior.
Keywords: J61; 330; Remittances; censored regression; altruism; Central America; Nicaragua; Rücküberweisung (Migranten); Altruismus; Geschlecht; Schätzung; Nicaragua